Research on Comprehensive Exploration Technology of Underground Soil Karst Cave. Issue 1 (February 2021) - Xi, Jianjun; Cui, Dandan
Abstract: Underground soi-karst caves are widely developed in China, especially in the southwestern region, and are relatively typical geological structures in limestone areas. It may cause adverse geological disasters such as landslides, ground fissures, ground collapses, mountain collapses, karst leaks, water loss, water inrush and mud out of mine pits, etc., which bring great hidden dangers to the survey and construction of foundation engineering. We analyze the mechanism of bad geological bodies for underground soil-karst caves, discuss the characteristics of several commonly used geophysical prospecting techniques for soil-karst cave exploration, such as high-density resistivity method, five-pole electric sounding method, and geological radar. Through the engineering examples, it is shown that the location and distribution of soil-karst caves can be effectively detected by using the above comprehensive exploration techniques, which take advantage of the differences in the electrical and magnetic properties of soil-karst caves.